Kazakhstan as a destination for Foreign Direct Investment : opportunities and insights - Safarova, Diana (2025)
The aim of this Bachelor's thesis is to evaluate Kazakhstan as a destination for foreign direct investment (FDI) by analyzing its business environment and competitiveness. The theoretical part defines FDI and its significance, examines key factors influencing FDI decisions, and reviews existing studies on Kazakhstan's FDI along with the historical development of foreign investment in the country since 1992. The analytical part employs a PESTEL analysis to assess Kazakhstan’s macro-environment across political, economic, social, technological, environmental, and legal factors, and a SWOT analysis to identify the country's strengths, weaknesses, opportunities, and threats in attracting investment. Additionally, a Pearson correlation analysis of data from 2012–2023 is conducted to investigate statistical relationships between FDI inflows and selected macroeconomic indicators (including GDP growth, corruption perception, inflation, exchange rates, interest rates, and oil prices). Finally, a comparative analysis benchmarks Kazakhstan’s investment attractiveness against other post-Soviet countries. The findings indicate that Kazakhstan offers a favorable investment climate characterized by political stability, strategic geographic location, and abundant natural resources. However, the thesis also highlights the need for ongoing reforms to diversify the economy and strengthen institutional frameworks in order to reduce dependence on the oil sector and enhance Kazakhstan’s position as a competitive and reliable destination for foreign investors.